From structure topology to chemical composition. XVIII. Titanium silicates: Revision of the crystal structure and chemical formula of betalomonosovite, a group-IV TS-block mineral from the Lovozero alkaline massif, Kola peninsula, Russia - Sokolova, Elena; Abdu, Yassir; Hawthorne, Frank C.; Genovese, Alessandro; Khomyakov, Alexander P.; CAMARA ARTIGAS, Fernando (The Canadian Mineralogist, 2015)
The crystal structure of betalomonosovite, ideally Na6□4Ti4 (Si2O7)2 [PO3 (OH)][PO2 (OH) 2]O2 (OF), a 5.3331(7), b 14.172 (2), c 14.509(2) Å, α 103.174(2), β 96.320(2), γ 90.278(2)°, V 1060.7(4) Å3, from the Lovozero alkaline massif, Kola peninsula, Russia, has been refined in the space group P1 to R = 6.64% using 3379 observed (Fo > 4σF) reflections collected with a single-crystal APEX II ULTRA three-circle diffractometer with a rotating-anode generator (MoKα), multilayer optics, and an APEX-II 4K CCD detector. Electron-microprobe analysis gave the empirical formula (Na5.39Ca0.36Mn0.04Mg0.01)Σ5.80 (Ti2.77Nb0.48Mg0.29Fe3+ 0.23Mn0.20Zr0.02Ta0.01)Σ4 (Si2.06O7)2 [P1.98O5 (OH) 3]O2 [O0.82F0.65 (OH) 0.53]Σ2, Dcalc. = 2.969 g cm-3, Z = 2, calculated on the basis of 26 (O + F) apfu, with H2O determined from structure refinement. The crystal structure of betalomonosovite is characterized by extensive cation and anion disorder: more than 50% of cation sites are partly occupied. The crystal structure of betalomonosovite is a combination of a titanium silicate (TS) block and an intermediate (I) block. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral) and exhibits linkage and stereochemistry typical for Group IV (Ti + Mg + Mn = 4 apfu) of the TS-block minerals. The I block is a framework of Na polyhedra and P tetrahedra which ideally gives {Na2□ 4 [PO3 (OH)][PO2 (OH) 2]} pfu. Betalomonosovite is an Na-poor OH-bearing analogue of lomonosovite, Na10Ti4 (Si2O7)2 (PO4)2O4. In the betalomonosovite structure, there is less Na in the I block and in the TS block when compared to the lomonosovite structure. The OH groups occur mainly in the I block where they coordinate P and Na atoms and in the O sheet of the TS block (minor). The presence of OH groups in the I block and in the TS block is supported by IR spectroscopy and bond-valence calculations on anions. High-resolution TEM of lomonosovite shows the presence of pervasive microstructural intergrowths, accounting for the presence of signals from H2O in the ...